2014
DOI: 10.1161/strokeaha.114.005227
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Emergency Hospital Visits and Hourly Changes in Air Pollution

Abstract: Background and Purpose-Few studies have examined the effect of hourly changes in air pollution on cardiovascular disease morbidity. We evaluated the associations between hourly changes in air pollution and the risks of several types of cardiovascular disease. Methods-We used a time-stratified case-crossover design. Study participants were 10 949 residents of the city of Okayama, Japan, aged ≥65 years who were taken to hospital emergency rooms between January 2006 and December 2010 for onset of cardiovascular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Many epidemiological studies linked short-term air pollution exposure to increased stroke onsets and emergency hospital admissions [2][3][4][5][6][7]. However, the particular effect of carbon monoxide (CO) on stroke was seldom reported.…”
Section: Introductionmentioning
confidence: 99%
“…Many epidemiological studies linked short-term air pollution exposure to increased stroke onsets and emergency hospital admissions [2][3][4][5][6][7]. However, the particular effect of carbon monoxide (CO) on stroke was seldom reported.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010 it is estimated 17 million first strokes occurred, an increase of 68% since 1990 (Feigin et al, 2014). The contribution of outdoor air pollution to stroke risk has been increasingly studied in recent years (Henrotin et al, 2007;Johnson et al, 2013;Johnson et al, 2010;Leiva et al, 2013;Lisabeth et al, 2008;Maheswaran et al, 2014;Maheswaran et al, 2012;Maheswaran et al, 2010;Qian et al, 2013;Wellenius et al, 2012;Yorifuji et al, 2013;Yorifuji et al, 2014;Yu et al, 2014).…”
mentioning
confidence: 99%
“…Several studies have found associations between short-term changes in air pollution and stroke risk (Leiva et al, 2013;Lisabeth et al, 2008;Qian et al, 2013;Wellenius et al, 2012;Yorifuji et al, 2014;Carlsen et al, 2013;Corea et al, 2012), in particular, PM 10 and/or PM 2.5 (PM b 10 μm and b 2.5 μm in diameter, respectively). A recent metaanalysis of 19 studies reported short-term changes in PM 10, but not PM 2.5, were associated with risk of ischaemic but not haemorrhagic strokes.…”
mentioning
confidence: 99%
“…Yorifuji et al in 2014 in Japan studied the effects of air pollution on cardiovascular patients and their hospital referral and found particulate matter exposure increases the risks of onset of cardiovascular and cerebrovascular disease (including hemorrhagic stroke) shortly after exposure [30] . Dominici et al in 2006 in the US estimated the risks of hospital admissions associated with exposure Pollution and Cardiovascular to PM 2.5 for Medicare enrollees and concluded that exposure to PM 2.5 in short-term increases the risk of hospital admission for cardiovascular and respiratory diseases [31] .…”
Section: Discussionmentioning
confidence: 99%